2018
DOI: 10.1016/j.jpain.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Research Design Characteristics of Published Pharmacologic Randomized Clinical Trials for Irritable Bowel Syndrome and Chronic Pelvic Pain Conditions: An ACTTION Systematic Review

Abstract: This article summarizes entry criteria and outcome measures and the clarity of reporting of these important design features in RCTs of irritable bowel syndrome and 3 common chronic pelvic pain conditions. These results can be used to improve design of future trials of these largely unaddressed pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover, evidence for the clinical relevance of experimental pain testing could lead to the development of more objective clinical markers of GWI and gastrointestinal symptoms that can be used in clinical trials. 3941 Somatic pain testing might be used to measure the changes in improvement following therapies given in clinical trials. These advances become even more important for an increasing number of veterans who are now serving in the Persian Gulf and are at a high risk of developing these chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, evidence for the clinical relevance of experimental pain testing could lead to the development of more objective clinical markers of GWI and gastrointestinal symptoms that can be used in clinical trials. 3941 Somatic pain testing might be used to measure the changes in improvement following therapies given in clinical trials. These advances become even more important for an increasing number of veterans who are now serving in the Persian Gulf and are at a high risk of developing these chronic pain disorders.…”
Section: Discussionmentioning
confidence: 99%
“…They included two RCTs including 306 patients with an odds ratio of 0.94 in those administered escitalopram and p<0.05 [13,14]; four systematic reviews each studying six to 15 RCTs with greater significance and low risk of bias [9,[15][16][17] and two meta-analyses [5,10]. One of which included seven RCTs with 346 patients comparing SSRI treatment with placebo treatment and showed that 54.5% (96/176) patients with SSRI trial demonstrated improvement in their symptoms (I²=49%, p=0.07) [5].…”
Section: Resultsmentioning
confidence: 99%
“…32,67 Of randomized controlled trials of pharmacotherapy interventions, a majority are industry-sponsored, and heterogeneic design precludes meta-analysis. 69 There is currently insufficient evidence to inform treatment recommendations other than heightened awareness of the presence of overlapping pain syndromes and treatment of all of these coincidentally.…”
Section: Resultsmentioning
confidence: 99%
“…Others calling for similar research note the importance of specifying entry criteria, endpoint reporting, and research methods to facilitate data abstraction for meta-analysis. 69 Until a widely accepted algorithm exists for the diagnosis and treatment of overlapping pain syndromes, we suggest the following for a practicing gynecologist: (1) screen patients presenting with chronic pelvic pain for multiple functional somatic syndromes using standardized criteria, (2) discuss appropriate referral patterns between colleagues from other disciplines (i.e., rheumatology, gastroenterology, pain specialists, psychiatry, physical therapy), (3) include nonpharmacologic interventions that have demonstrated benefit in individual pain disorders (i.e., education, exercise, cognitive behavioral therapy), and (4) consider pharmacologic therapies with central targets (tricyclic antidepressants, SNRIs, and gabapentinoids). Once these goals have been accomplished, an institutional algorithm for evaluation, treatment, and referral may arise, which should be studied.…”
Section: Resultsmentioning
confidence: 99%